2006
DOI: 10.1095/biolreprod.105.049494
|View full text |Cite
|
Sign up to set email alerts
|

Previtellogenic Oocyte Growth in Salmon: Relationships among Body Growth, Plasma Insulin-Like Growth Factor-1, Estradiol-17beta, Follicle-Stimulating Hormone and Expression of Ovarian Genes for Insulin-Like Growth Factors, Steroidogenic-Acute Regulatory Protein and Receptors for Gonadotropins, Growth Hormone, and Somatolactin1

Abstract: Body growth during critical periods is known to be an important factor in determining the age of maturity and fecundity in fish. However, the endocrine mechanisms controlling oogenesis in fish and the effects of growth on this process are poorly understood. In this study interactions between the growth and reproductive systems were examined by monitoring changes in various components of the FSH-ovary axis, plasma insulin-like growth factor 1 (Igf1), and ovarian gene expression in relation to body and previtell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
102
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(109 citation statements)
references
References 69 publications
7
102
0
Order By: Relevance
“…In addition to these roles, Gh has been implicated, directly and indirectly, in the regulation of reproductive processes in several vertebrate taxa. In salmonid fishes, several studies have shown that growth rate at critical periods determines whether animals will undergo gonadal maturation and initiation of spermatogenesis or secondary ovarian follicle growth, an effect that may be mediated through plasma levels of Igf (Campbell et al 2003(Campbell et al , 2006. Gh and Igf1 have also been shown to act on the gonad to stimulate steroid production (Lubzens et al 2010, Schulz et al 2010 and Igf1 is involved in the regulation of final oocyte maturation (Lubzens et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these roles, Gh has been implicated, directly and indirectly, in the regulation of reproductive processes in several vertebrate taxa. In salmonid fishes, several studies have shown that growth rate at critical periods determines whether animals will undergo gonadal maturation and initiation of spermatogenesis or secondary ovarian follicle growth, an effect that may be mediated through plasma levels of Igf (Campbell et al 2003(Campbell et al , 2006. Gh and Igf1 have also been shown to act on the gonad to stimulate steroid production (Lubzens et al 2010, Schulz et al 2010 and Igf1 is involved in the regulation of final oocyte maturation (Lubzens et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In general, reproduction is closely related to body growth (5)(6)(7)(8), and gonads are recognized as important organs for growth. However, few examples showing a clear relationship between the gonad and body growth have been published.…”
mentioning
confidence: 99%
“…They estimated growth history from annuli of scales in hatchery-arrived chum salmon, and showed that the recent growth rate is the most important factor for oceanic fish to determine whether mature or not mature in the subsequent spawning period. Since the plasma levels of IGF-I correlated well with the growth rates and body sizes in immature and early maturing salmonids (Beckman et al, 1998;Shimizu et al, 2000;Campbell et al, 2003;Campbell et al, 2006), the plasma IGF-I levels may be an important somatotropic signal that interrelated with the onset of spawning migration.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this discrepancy is that gonads themselves influence circulating IGF-I levels, because the gonads are suggested to be one of the sources of IGF-I (Le Gac et al, 1996;Campbell et al, 2006), and actually express GH receptors (Fukada et al, 2005). The role of developing gonads in IGF-I secretion remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation